Energy colonialism and the role of the global in local responses to new energy infrastructures in the UK: a critical and exploratory empirical analysis - Batel, S.; Devine-Wright, P. (Antipode, 2017)
Governments, namely in the global North, are fostering the deployment of large-scale low carbon and associated energy infrastructures (EIs), such as power lines, to mitigate climate change. However, when infrastructures are to be deployed, opposition is often found. Environmental justice—involving issues of distributive and procedural justice and recognition—and associated inter-group relations, has been identified as a key aspect for local opposition. However, research has rarely examined local perceptions of environmental justice and associated practices, such as energy colonialism, within a global perspective. Adopting an interdisciplinary approach, we examine if and how different-level intergroup relations and collective narratives shape people's social-psychological and geographical imaginaries and responses to EIs. Focus groups were conducted with community members affected by proposals to construct high-voltage power lines in the UK. Analyses suggest that narratives around England's colonial history—within Britain and beyond Britain—shape responses to EIs.